Control Voltage Effect on Operational Characteristics of Vehicle Magnetorheological Damper - Le, Van Nghia; Nguyen, Trong Hoan; Dam, Hoang Phuc; Nguyen, Trung Kien; Kharytonchyk, S. V.; Kusyak, V. A. (БНТУ, 2024)
Considering the increasingly large-scale application of magnetic fluids in various industries, we can confidently state that in the near future magnetorheological dampers will be widely used in adaptive automotive suspensions due to their operational flexibility and simplicity of controlling damping forces by changing the magnetic fluid properties according to parameters of surrounding electromagnetic field. The antivibration efficiency during operation is achieved by regulating the hydraulic resistance of the “magnetic” shock absorber by applying voltage to the windings of its coil. In addition to the physical properties of the oil used in the “magnetic” shock absorber, the viscosity of the working magnetorheological fluid is greatly influenced by the shape of the control signal. The paper focuses on the theoretical aspects of constructing a mathematical model of ac magnetorheological damper and presents the results of a computer experiment to assess effectiveness of its use as part of the adaptive suspension a passenger vehicle. In this case, the actual parameters of the “magnetic” shock absorber, used in modeling the dynamic process, were determined experimentally on a test bench, and the adequacy of the developed mathematical model was confirmed by the results of a semi-natural experiment. Using a verified model, the magnetorheological damper characteristics were obtained and compared for various forms of control signal, including rectangular voltage pulses of various frequencies and duty cycles, sinusoidal pulses and constant voltage signals. The analysis of the antivibration efficiency was carried out on the basis of the developed “quarter” model of a semi-active car suspension with a verified submodel of a magnetorheological damper integrated into its structure. Moreover, the simulation scenarios were based on the selected strategy for controlling the voltage supplied to the windings of the “magnetic” shock absorber. As the results of theoretical and experimental studies have shown in terms of energy consumption, expansion of the working area of the damping characteristic and achieving smooth control of the damping force, the most effective is the use of a sinusoidal pulse voltage signal in the control circuit, which ensures a reduction in both the amplitude and damping time of oscillations. However, when de-signing and manufacturing a controller, creating a pulse modulator for generating sinusoidal pulses coinciding in phase and frequency with the vibrations of the car body is very difficult due to the random nature of external disturbances from the road surface. When a constant voltage is applied to the magnetorheological damper winding, the damping properties of the suspension are also improved compared to the basic design based on a traditional hydraulic shock absorber. Moreover, there is a proportional relationship between the voltage supplying the damper, the amplitude and damping time of the vibrations of the car body is observed. An increase in the control signal voltage from 1 to 2 V leads, in comparison with passive control of a magnetic shock absorber, to a decrease in the maximum amplitude of vibrations of the car body by 6.25 and 11.25 %, respectively, and a decrease in the vibration damping time by 0.72 and 1.41 s.
Влияние управляющего напряжения на эксплуатационные характеристики магнитореологического демпфера автомобиля